Multi‐frequency (S, X, Q and W‐band) EPR and ENDOR Study of Vanadium(IV) Incorporation in the Aluminium Metal–Organic Framework MIL‐531. Issue 14 (20th August 2015) - Nevjestić, Irena; Depauw, Hannes; Leus, Karen; Kalendra, Vidmantas; Caretti, Ignacio; Jeschke, Gunnar; Van Doorslaer, Sabine; Callens, Freddy; Van Der Voort, Pascal; Vrielinck, Henk
Abstract Doping the well‐known metal–organic framework MIL‐53(Al) with vanadium(IV) ions leads to significant changes in the breathing behaviour and might have repercussions on the catalytic behaviour as well. To understand the properties of such a doped framework, it is necessary to determine where dopant ions are actually incorporated. Electron paramagnetic resonance (EPR) and electron–nuclear double resonance (ENDOR) are applied to reveal the nearest environment of the paramagnetic vanadium(IV) dopant ions. EPR spectra of as‐synthesised vanadium‐doped MIL‐53 are recorded at S‐, X‐, Q‐ and W‐band microwave frequencies. The EPR spectra suggest that at low dopant concentrations (1.0–2.6 mol %) the vanadium(IV) ions are well dispersed in the matrix. Varying the vanadium dopant concentration within this range or the dopant salt leads to the same dominant EPR component. In the ENDOR spectra, hyperfine (HF) interactions with 1H, 27Al and 51V nuclei are observed. The HF parameters extracted from simulations strongly suggest that the vanadium(IV) ions substitute Al in the framework.